PENGARUH SUPERVISI SEKOLAH, MOTIVASI KERJA DAN KONSEP DIRI TERHADAP KOMPETENSI PROFESIONAL GURU PADA SMPN 4 SATAP MINASATENE KABUPATEN PANGKEP - Tanda Wali (STKIP Pembangunan Indonesia Makassar, 2022)
The objectives of this study are as follows: 1. To find out the effect of school supervision on the professional competence of teachers at SMPN 4 Satap Minasatene. 2. To find out the influence of teacher work motivation on teacher professional competence at SMPN 4 Satap Minasatene. 3. To determine the effect of self-concept on the professional competence of teachers at SMPN 4 Satap Minasatene. 4. To determine the effect of school supervision, work motivation, and self-concept on teacher professional competence at SMPN 4 Satap Minasatene. Data collection techniques using questionnaires, documentation, observation and interviews. The research method used is descriptive quantitative with multiple linear regression data analysis techniques. The results of the research that have been carried out indicate that the results of this study are concluded that: 1. There is an effect of School Supervision on the Professional Competence of Educators at SMPN 4 Satap Minasatene Pangkep Regency. 2. There is an influence of teacher work motivation on the Professional Competence of Educators at SMPN 4 Satap Minasatene Pangkep Regency. 3. There is an effect of self-concept on the Professional Competence of Educators at SMPN 4 Satap Minasatene Pangkep Regency. 4. School supervision, motivation and self-concept have a simultaneous effect on the Professional Competence of Educators at SMPN 4 Satap Minasatene Pangkep Regency. Keywords: Supervision, motivation, self concept and competence